Personal Data Protection for Online Job Seekers in the Mode of Freelance Job Vacancy Fraud - Ela Suryani; Rasji (Dinasti Research, 2024)
Digitalization has brought convenience in job search, but it also raises the risk of misuse of personal data, especially through the fraudulent mode of freelance job vacancies. This research aims to analyze the legal responsibility of digital platforms in protecting users' personal data as well as the implementation of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) in handling cybercrime cases. The research method used is qualitative descriptive, with a literature study approach to relevant regulations and cases that occur. The results of the study show that digital platforms have an obligation to ensure the security of user data, including by implementing a verification system and preventing data leaks. The PDP Law provides a strong legal basis in protecting the rights of personal data owners, but its implementation still requires increased public awareness and stricter supervision.